hiPSC-derived cardiomyocytes as a model to study the role of small-conductance Ca2+-activated K+ (SK) ion channel variants associated with atrial fibrillation - Babini, Hosna; Jiménez-Sábado, Verónica; Stogova, Ekaterina; Arslanova, Alia; Butt, Mariam; Dababneh, Saif; Asghari, Parisa; Moore, Edwin D. W.; Claydon, Thomas W.; Chiamvimonvat, Nipavan; Hove-Madsen, Leif; Tibbits, Glen F. (Frontiers in Cell and Developmental Biology, 2024)
Atrial fibrillation (AF), the most common arrhythmia, has been associated with different electrophysiological, molecular, and structural alterations in atrial cardiomyocytes. Therefore, more studies are required to elucidate the genetic and molecular basis of AF. Various genome-wide association studies (GWAS) have strongly associated different single nucleotide polymorphisms (SNPs) with AF. One of these GWAS identified the rs13376333 risk SNP as the most significant one from the 1q21 chromosomal region. The rs13376333 risk SNP is intronic to the KCNN3 gene that encodes for small conductance calcium-activated potassium channels type 3 (SK3). However, the functional electrophysiological effects of this variant are not known. SK channels represent a unique family of K + channels, primarily regulated by cytosolic Ca 2+ concentration, and different studies support their critical role in the regulation of atrial excitability and consequently in the development of arrhythmias like AF. An important goal is to elucidate whether the rs13376333 risk SNP is a gain-of-function (GoF) or a loss-of-function (LoF) variant. A better understanding of the functional consequences associated with these SNPs could influence clinical practice guidelines by improving genotype-based risk stratification and personalized treatment. Although research using native human atrial cardiomyocytes and animal models has provided useful insights, each model has its limitations. Therefore, there is a critical need to develop a model that represents human physiology more accurately. Generating cardiomyocytes derived from hiPSCs (hiPSC-CMs) has revealed the underlying causes of various cardiovascular diseases and identified treatment opportunities that were not possible using in vitro or in vivo studies with animal models. Thus, the ability to generate atrial cardiomyocytes and atrial tissue derived from hiPSCs from human/patients with specific genetic diseases, incorporating novel genetic editing tools to generate isogenic controls and organelle-specific reporters, and 3D bioprinting of atrial tissue are essential to study AF pathophysiological mechanisms. In this review, we will first give an overview of SK-channel function, its role in atrial fibrillation and outline pathophysiological mechanisms of KCNN3 risk SNPs and then highlight the advantages of using the hiPSC-CM model to investigate SNPs associated with AF, while addressing limitations and best practices for rigorous hiPSC studies.